2016
DOI: 10.1051/matecconf/20168107001
|View full text |Cite
|
Sign up to set email alerts
|

Projects Delay Factors of Saudi Arabia Construction Industry Using PLS-SEM Path Modelling Approach

Abstract: Abstract. This paper presents the development of PLS-SEM Path Model of delay factors of Saudi Arabia construction industry focussing on Mecca City. The model was developed and assessed using SmartPLS v3.0 software and it consists of 37 factors/manifests in 7 groups/independent variables and one dependent variable which is delay of the construction projects. The model was rigorously assessed at measurement and structural components and the outcomes found that the model has achieved the required threshold values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Notably, lack of qualified and experienced professionals was considered as a key reason for failures according to research conducted by Al-Kharashi and Skitmore (2009) in Saudi Arabia. Abdul Rahman et al. (2016), on the other hand, identified 58 factors that lead to the failure of mega construction projects in Makkah.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, lack of qualified and experienced professionals was considered as a key reason for failures according to research conducted by Al-Kharashi and Skitmore (2009) in Saudi Arabia. Abdul Rahman et al. (2016), on the other hand, identified 58 factors that lead to the failure of mega construction projects in Makkah.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The respondents were 128; Table 2 provides relevant demographic information. The researcher measured internal consistency and reliability using two measurements including Cronbach's alpha and composite reliability (Purwanto & Sudargini, 2021;Rahman et al, 2016). The Cronbach's alpha coefficient and the composite reliability for each construct in a measurement model (Table 8) are considered satisfactory if they are equal to or higher than 0.7.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Alajmi and Memon (2022) employed a critical analysis of the literature review and recommended that ineffective communication, lack of worker's expertise, monetary issues, delays in material procurement and supplies, management issues, slow decision-making and inadequate planning are major risk concerns. Rahman et al (2016) employed structural equation modeling and found that the contractual and project management factors, owner and consultants factors, labor factors, communication and information technological factors, drawings and documentation factors, site management factors and materials and machines factors are the significant risk factors.…”
Section: Risk Factors In Saudi Arabiamentioning
confidence: 99%